COVID-19: Vaccine Hesitancy in Africa and the Way Forward - Omeiza, Lukman Ahmed; Azad, Abul Kalam; Kozak, Kateryna; Mafo, Abaniwo Rose; Mamudu, Ukashat; Oseyemen, Daniel Aikhonmu (Problemy Ekorozwoju, 2022)
COVID-19 pandemic took the world by storm in late 2019, scientists and health authorities across the globe struggle to contain the deadly virus. Socio-economic activities across the globe were partly halted as countries around the world introduce various forms of restrictions to contain the spread of the COVID-19 virus. Most developing countries’ economies, especially in Africa, slid into recession, unemployment among Africa countries skyrocketed to an all-time high, and famine and starvation were beginning to knock harder on poorer nations around the world. The race to develop a vaccine was pressing harder; developed countries continue to pump more money to help develop a vaccine within the shortest period of time, as that seems the only viable solution to the economic downturn of the global world. Finally, vaccines were developed and proved to have high efficacy. This has helped reverse the negative trend of the global economy caused by the COVID-19 pandemic. This vaccine faced a lot of global scrutinies, but many people have refused to get vaccinated and have also rejected the idea of making COVID-19 vaccination compulsory for citizens worldwide. This study analyzes the challenges posed by this ugly trend of COVID-19 vaccine hesitancy in African countries, its socio-economic consequences and the way forward.